Exceptional strength-ductility synergy at room and liquid nitrogen temperatures of Al7.5Co20.5Fe24Ni24Cr24 high-entropy alloy with hierarchical precipitate heterogeneous structure - Chu, Chenliang; Chen, Weiping; Huang, Liran; Wang, Hao; Chen, Ling; Fu, Zhiqiang (International journal of plasticity, 2024)
•Hierarchically precipitated heterostructure was obtained by thermo-mechanical treatment.•Exceptional strength-ductility synergies were achieved at both 293 K and 77 K.•Hetero-deformation-induced hardening stress fosters deformation twins formation as plastic strain increase.•The interplay of dislocations, stacking faults and deformation twins improves the strain-hardening at 293 K.•Multiple deformation modes were activated to sustain the strain-hardening at 77 K. The study of alloys exhibiting noteworthy strength-ductility synergy at ambient and cryogenic temperatures has been a persistent area of interest in materials engineering. This interest extends to the recent development of high-entropy alloys (HEAs). The current investigation delves into the impact of diverse thermo-mechanical treatments on the phase and microstructure evolution in a face-centered cubic (FCC) Al7.5Co20.5Fe24Ni24Cr24 HEA. The transition from solid-solution annealing to recrystallization annealing leads to the formation of the desired hierarchical B2+L12+σ precipitates, accompanied by a heterogeneous FCC matrix. The initiation of the B2 phase originates from nucleation on defect-rich sites, such as deformation bands. However, the coherent L12 phase homogeneously forms in the FCC matrix at intermediate temperature aging, as these sites are scarce or occupied. A heterogeneous structure emerges from the transition in annealing temperatures and the pinning effect of the B2 precipitates. The resulting heterogeneous structure exhibits an exceptional strength-ductility synergy at both room and liquid nitrogen (LN2) temperatures. This is evident in its mechanical properties with a yield strength of ∼717 MPa / ∼1109 MPa, an ultimate tensile strength of ∼1086 MPa / ∼1609 MPa, and an elongation of ∼34.3 % / ∼43.2 % at room / LN2 temperatures. The formation of deformation twins (DTs) is facilitated by localized stress buildup from hetero-deformation-induced (HDI) hardening stress at room temperature. The exceptional strength and ductility at LN2 temperature are attributed to a combination of factors. These include a high-density of stacking faults (SFs), DTs, and their interactions, including those with precipitates, SFs-based substructures, and Lomer-Cottrell locks. These multiple deformation mechanisms ensure consistent and sustained strain-hardening even under substantial strain. This paper sheds light on the complex interplay of microstructure, deformation mechanisms, and mechanical properties in the Al7.5Co20.5Fe24Ni24Cr24 HEA, potentially guiding the development of ultra-strong yet ductile alloys for cryogenic applications.